Ideología del presente - Mallo, Jorge (2018)
There will always be prospects for intervention in the globalized world with the rules of the system itself. The ideologies are linked to the categories of time and space, but a semiotic view of the cultural universes can approach their understanding from another analytical place. The methodological allows to appreciate the new ideological constructions. In the case of the ideology of the present that occupies us, the premise is to put in crisis a series of concepts that are at a certain speed and vertiginous.